Molecular profile and cell cycle in MCF-7 and MCF‑7/Dox cells exposed to conventional and liposomal forms of doxorubicin - Rusetskaya, N.V.; Lukyanova, N.Yu.; Chekhun, V.F. (Experimental Oncology, 2009)
Aim: To compare the molecular profile and cell cycle of sensitive and resistant to doxorubicin MCF-7 breast cancer cells upon exposition to conventional or liposome-encapsulated forms of doxorubicin. Methods: МТТ-test, immunocytochemistry, flow cytometry. Results: In sensitive MCF-7 cells the exposure to conventional but not liposomal form of doxorubicin decreased metallothionein (MT) expression demonstrating activation of MT-detoxification system. In doxorubicin-resistant cells (MCF-7/Dох) MT expression drastically decreased. Conventional but not liposomal form of doxorubicin reduced the levels of expression of steroid hormones receptors on MCF-7 sensitive cells. The exposure of ΜCF-7 cells to conventional form of doxorubicin resulted in the decrease of p53 expression and the increase of Bcl-2 expression. In MCF-7/Dох cells neither conventional nor liposomal form of doxorubicin altered Bcl-2 expression. The exposure of MCF-7 but not MCF-7/Dох to doxorubicin in conventional form caused cell cycle arrest in G0/G1. Upon exposure to doxorubicin in liposomal form, cell cycle blockage in G0/G1 phase was observed in both sensitive and resistant sublines. Conclusion: The differential effects of the conventional and liposomal forms of doxorubicin in sensitive and resistant cells have been demonstrated. Exposure of MCF-7 and MCF-7/Dох cells to doxorubicin in liposomal form alters the molecular profile and cell distribution over cell cycle phases.